Karakteristik Buah Dan Biji Cabai Rawit (Capsicum frustescens L.) Yang Diberi Pupuk Organik Cair Rebung Bambu Terfermentasi Ragi Tempe - Antonius Buksalwembun; Vivin Andriani (Universitas PGRI Adi Buana Surabaya, 2020)
Cayenne pepper (Capsicum frustescens L.) is one of the important vegetable crops for the community as a flavor enhancer in daily cooking. The purpose of this study was to determine the effect of liquid organic fertilizer application of fermented tempeh bamboo yeast on the characteristics of fruit and seeds as well as yields of cayenne pepper. This research was experimental using RAL with 4 treatments of 0 ml / l, 5 ml / l, 10 ml / l and 15 ml / l of liquid organic fertilizer, fermented bamboo shoots, fermented tempeh, 6 times. The results of this study showed that the production of cayenne pepper with a concentration of 10 ml / l resulted in the production of the best number of fruits with an average of 68.17 grams, while there was a study of the number of seeds showing that a concentration of 10 ml / l produced the best number of seeds with an average of 1.584. Keywords : Cayenne pepper (Capsicum frustescens L.); bamboo shoots; fermentation; tempeh yeast; production..